Emerging Trends and Challenges in Digital Crime: A Study of Cyber Criminal Tactics and Countermeasures - Adam At Thur Jasson Cassidy; Anis Fuad; Muhammad Ulil Abshor As Shofy (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2024)
The rise of digital crime, particularly cybercrime, poses significant challenges to individuals, organizations, and societies worldwide. This study explores emerging trends and challenges in digital crime, focusing on the tactics employed by cybercriminals and the countermeasures developed to mitigate these threats. The urgency of this research lies in the increasing sophistication and frequency of cyberattacks, which threaten sensitive data, financial assets, and critical infrastructure. The objectives of this study are to analyze current trends in cybercrime, identify the most prevalent tactics used by cybercriminals, and examine effective countermeasures and strategies implemented by organizations and law enforcement agencies. This research adopts a literature review methodology, synthesizing findings from academic research, industry reports, and government publications. Key findings highlight the evolving nature of cyber threats, including phishing attacks, ransomware campaigns, and data breaches. Effective countermeasures include cybersecurity frameworks, incident response protocols, and technological advancements in threat detection and prevention. The study underscores the importance of ongoing research and collaboration among stakeholders to address the dynamic landscape of digital crime and safeguard digital ecosystems against emerging threats